Effect of Particle Size and HCl Concentration on the Demineralization Process Chitosan Shell Crab (Portunus pelagicus) - Kurniawan, Andry (University of Brawijaya, 2019)
This study is intended to find the best results and HCl concentration in making chitosan skin crust (Portunus pelagicus). The research method used Randomized Block Design with two factors consisting of three levels. The first factor were particle sizes (100, 80 and 60 mesh) and the second facto were HCl concentrations (1, 1.25 and 1.5M) in the demineralization process with 2 replications so that there are 18 units of experiment. Observations included yield, water content, ash content and deacetylation degree. The results showed that the optimum condition for chitosan production is particle size 60 mesh and HCl concentration 1.5 M with yield 17.20%, water content 4.23% ash content 20.83% and deacetylation degree of 65%. The 60 mesh particle size has given optimal results and the higher the concentration of HCl used is more effective in reducing ash content.Â Â